Zinc ferrate nanoparticles for applications in medicine: synthesis, physicochemical properties, regulation of macrophage functions, and in vivo safety evaluation. Issue 10 (25th November 2020) - Wang, Yu; Liu, Yajie; Li, Jiajia; Xu, Xiaoqing; Li, Xinru
Abstract: Zinc ferrate nanoparticles (ZnFe2 O4 NPs) have attracted enormous interest as potential nanomaterials. The purpose of this study was to examine the in vitro macrophages toxicity, in vivo safety, and immunogenicity. Three kinds of ZnFe2 O4 NPs with different shapes (round, litchi, and raspberry), nano-sizes, and pores were successfully prepared. In vitro experiments showed that ZnFe2 O4 NPs caused no cytotoxicity against the RAW 264.7 cells up to administered dose of 200 μg/mL, enhanced proinflammatory cytokine TNF-α, and costimulatory marker CD86 expression in the RAW 264.7 cells. Interestingly, ZnFe2 O4 NPs reduced ROS expression, which was inconsistent with common metal oxide NPs such as iron oxide (Fe3 O4 ) NPs and zinc oxide (ZnO) NPs. ZnFe2 O4 NPs improved the RAW 264.7 cells phagocytosed more neutral red. There was no obvious difference in body weight, the number of immune cells, organ index, and expression of inflammatory factors in serum of rats administrated intravenously and subcutaneously on day 21 after treatment by ZnFe2 O4 NPs in comparison with the blank control. These results demonstrated that ZnFe2 O4 NPs slightly enhanced the function of the RAW 264.7 cells in vitro but caused no obvious toxicity to macrophages as well as rat blood cells, and low immunogenicity in rats, suggesting that ZnFe2 O4 NPs as a biocompatible nanomaterials achieved potential for bioapplication in the future.